2011
DOI: 10.1590/s1519-566x2011000100020
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and Sublethal Effects of Methoxyfenozide on the Development, Survival and Reproduction of the Fall Armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae)

Abstract: The lethal and sublethal effects of the ecdysone agonist methoxyfenozide on the fall armyworm, Spodoptera frugiperda (J. E. Smith), were investigated by feeding a methoxyfenozide-treated diet to ifth instars until pupation in doses corresponding to the LC 10 and LC 25 for the compound. Larval mortality reached 8% and 26% in the low and high concentration groups, respectively, on the seventh day of the experiment. A progressive larval mortality of 12% for the LC 10 and 60% for the LC 25 was observed before pupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 26 publications
7
13
1
Order By: Relevance
“…Reduction in fecundity noticed in this study was also reported by several investigators (Pineda et al, 2007;Rastegari and Subrahmanyam, 2008;Pineda et al, 2009;Enriquez et al, 2010;Shahout et al, 2011;and Zarate et al, 2011) on Spodoptera species. Acheuk et al, 2012 suggested moreover, that chitin deficiency weakened the exoskeleton and muscle attachment in the embryo, rendered it incapable of withstanding the strong pressure required for successful hatching, thus reduced hatching of eggs laid by treated females.…”
Section: Indoxacarbsupporting
confidence: 91%
“…Reduction in fecundity noticed in this study was also reported by several investigators (Pineda et al, 2007;Rastegari and Subrahmanyam, 2008;Pineda et al, 2009;Enriquez et al, 2010;Shahout et al, 2011;and Zarate et al, 2011) on Spodoptera species. Acheuk et al, 2012 suggested moreover, that chitin deficiency weakened the exoskeleton and muscle attachment in the embryo, rendered it incapable of withstanding the strong pressure required for successful hatching, thus reduced hatching of eggs laid by treated females.…”
Section: Indoxacarbsupporting
confidence: 91%
“…shorter duration indicates faster rate and vice versa. As reported by many studies, larval duration in several insect species (holometabolous or hemimetabolous) had been prolonged as a response to the action of different IGRs, such as the fall armyworm Spodoptera frugiperda as a response to methoxyfenozide (Zarate et al, 2011); S. littoralis as a response to novaluron (Ghoneim et al, 2015) and cyromazine (Tanani et al, 2015); G. pyloalis as a response to lufenuron (Aliabadi et al, 2016); C. pipiens as a response to methoxyfenozide (Hamaidia and Soltani, 2016); C. cephalonica as a response to fenoxycarb (Begum and Qamar, 2016); P. gossypiella as a response to pyriproxyfen (Sabry and Abdou, 2016) and novaluron . Also, treatment of some insects with anti-JH compounds resulted in prolongation of the larval duration, such as 5 th nymphal instar in O. fasciatus after treatment with PI (Bowers and Aldrich, 1980); 4 th instar nymphs of S. gregaria after treatment with PII (Eid et al, 1982); three latter instars of the fall webworm Hyphantria cunea after treatment with fluoromevalonate (Farag and Varjas, 1983); 6 th instar larvae of S. mauritia after treatment with PII (Mathai and Nair, 1984); 5 th instar nymphs of the grasshopper Aiolopus thalassinus after treatment with PIII (Osman, 1988); larval period of S. litura after treatment with PI, PII and ethoxyprecocene (a synthetic analog of P II) (Srivastava and Kumar, 1999); etc.…”
Section: Affected Developmental Durationsmentioning
confidence: 76%
“…This could be refer to the natural of IGRs which were developed in order to inhibit or to disrupt the insect growth, the molt and or the metamorphosis (Salem et al, 1997 andDhadialla et al, 1998). These results could be explained by the accumulation and persistence of ecdysone agonists in the larval tissue until the pupal molt, at which point the agonist kills the insect (Zarate et al, 2011). In addition, Sundaram et al, (2002) reported the presence of an ecdysone receptor complex in the lepidopteran pupae, also, he mentioned that larval stage is susceptible to ecdysone agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Larval mortality was significantly higher on chromafenozide after 10 days of treatment compared to essential plant oils, while there was no significant different between chromafenozide and novaluron and methoxyfenozide. These results could be explained by the accumulation and persistence of ecdysone agonists in the larval tissue until the pupal molt, at which point the agonist kills the insect (Zarate et al, 2011). Pineda et al 2007 mentioned that treating early instars of cotton leafworm with methoxyfenozide leading to consequent larval mortality.…”
Section: Discussionmentioning
confidence: 99%